Pathway of effects of adverse childhood experiences on the poly-drug use pattern among adults using drugs: A structural equation modeling - Li, Jing; He, Jianhui; Wang, Pei; Li, Jiashuang; Zhang, Yunjia; You, Jing; Chongsuvivatwong, Virasakdi (Frontiers in Public Health, 2023)
Introduction Adverse childhood experiences (ACEs) are associated with an increased risk of poly-substance use among drug-using adults. However, there is a paucity of literature on a direct or indirect relationship between ACEs and drug use patterns. We thus aimed to identify the pathway of effects of ACEs on drug use patterns in adults by the structural equation model (SEM). Methods A cross-sectional study was conducted by respondent-driving sampling and consecutive sampling among adult drug users in Southwest China in 2021. Descriptive, univariate, and SEM analyses were performed by R software 4.2.1. Results Of 406 participants recruited from a drug abuse clinic, the average age was 34 years. The majority of the participants were male patients (98.3%) from ethnic minorities (79.6%), who were unmarried (71.6%) and employed (81.2%). Nearly 95.5% experienced ACEs with 46.6% of them reporting four or more ACEs. The median value of self-perception of drug abuse score, friend drug use score, and drug use score was 8.0 (3.0, 11.0), 1.0 (0.0, 1.0), and 1.0 (1.0, 2.0) respectively. In the confirmatory analysis part of SEM, the construct of latent variables fitted well with the data. Poly-drug use was significantly and directly affected by three predictors including monthly incomes (β = 0.09), friend drug use (β = 0.50), and ACEs (β = 0.11). The indirect effect of ACEs passing through self-perception of drugs (β = 0.09) was not significant. Discussion ACEs have an independent and direct effect on the drug user for poly-drug use apart from the effect of drug-using friends and family income.